Multi-Omics Analysis Provides Insight into the Possible Molecular Mechanism of Hay Fever Based on Gut Microbiota. (August 2022) - Han, Pei; Li, Li-Sha; Wang, Zi-Xi; Xi, Lin; Yu, Hang; Cong, Lin; Zhang, Zheng-Wei; Fu, Jie; Peng, Ran; Pan, Li-Bin; Ma, Shu-Rong; Wang, Xue-Yan; et al.
Abstract: Due to the worldwide epidemic of allergic disease and a cure nowhere in sight, there is a crucial need to explore its pathophysiological mechanisms. As allergic disease has been associated with gut dysbiosis, we searched for a possible mechanism from the perspective of the molecular interface between host and microbiota with concurrent metabolomics and microbiome composition analysis. Sprague-Dawley rats were injected with Artemisia pollen extract to stimulate a hyper reaction to pollen. This hyper reaction decreased the circulation of valine, isoleucine, aspartate, glutamate, glutamine, indole-propionate (IPA), and myo-inositol, and reduced short-chain fatty acids (SCFAs) in feces. Several beneficial genera belonging to Ruminococcaceae, Lachnospiraceae, and Clostridiales declined in the model group, whereas Helicobacter and Akkermansia were only expressed in the model group. Furthermore, the expression of intestinal claudin-3 and liver fatty acid binding protein was downregulated in the model group and associated with metabolic changes and bacteria . Our results suggest that alterations in amino acids as well as their derivatives (especially valine, and IPA which is the reductive product of tryptophan), SCFAs, and the gut microbiome (specifically Akkermansia and Helicobacter ) may disrupt the intestinal barrier function by inhibiting the expression of claudin proteins and affecting the mucus layer, which further results in hay fever.